Erasmus University Rotterdam wrestles with sustainability strategy - Wijen, Frank, (SAGE Knowledge. Cases., 2013)
Erasmus University Rotterdam (EUR) is in the midst of a sustainability dilemma. The university is in a stage of transition, shifting focus from the city to the world stage. EUR's current environmental sustainability policy needs more impetus. The university wants to incorporate sustainability into its new strategy (2013-2018) to become more competitive. But with reduced government funding, EUR has fewer resources to promote sustainability. The crux of EUR's dilemma is how more than 20,000 EUR students and 2,500 employees can be sensitised to, and induced to act upon, sustainability - even though it is not necessarily a priority for them. EUR is a university with a strong business, economics, law and medicine focus - therefore, the students' primary goal is traditionally a good career first. The crucial question is thus how to win a place in the students' and employees' hearts and minds for sustainability in the broader sense.